Ferritin in iron containing granules from the fat body of the honeybees Apis mellifera and Scaptotrigona postica - Keim, C. N.; Cruz-Landim, C.; Carneiro, F. G.; Farina, M. (Elsevier B.V., 2002)
It is already known that the behaviour of the honeybee Apis mellifera is influenced by the Earth's magnetic field. Recently it has been proposed that iron-rich granules found inside the fat body cells of this honeybee had small magnetite crystals that were responsible for this behaviour. In the present work, we studied the iron containing granules from queens of two species of honeybees (A. mellifera and Scaptotrigona postica) by electron microscopy methods in order to clarify this point. The granules were found inside rough endoplasmic reticulum cisternae. Energy dispersive X-ray analysis of granules from A. mellifera showed the presence of iron, phosphorus and calcium. The same analysis performed on the granules of S. postica also indicated the presence of these elements along with the additional element magnesium. The granules of A. mellifera were composed of apoferritin-like particles in the periphery while in the core, clusters of organised particles resembling holoferritin were seen. The larger and more mineralised granules of S. postica presented structures resembling ferritin cores in the periphery, and smaller electron dense particles inside the bulk. Electron spectroscopic images of the granules from A. mellifera showed that iron, oxygen and phosphorus were co-localised in the ferritin-like deposits. These results indicate that the iron-rich granules of these honeybees are formed by accumulation of ferritin and its degraded forms together with elements present inside the rough endoplasmic reticulum, such as phosphorus, calcium and magnesium. It is suggested that the high level of phosphate in the milieu would prevent the crystallisation of iron oxides in these structures, making very unlikely their participation in magnetoreception mechanisms. They are most probably involved in iron homeostasis. (C) 2001 Elsevier B.V. Ltd. All rights reserved.
Keywords: iron-rich granules; magnetoreception; honeybee; ferritin; fat body; biomineralisation